Etika Bisnis Dan Tanggung Jawab Sosial Perusahaan Di Indonesia: Teori Dan Realitas - Sofia Yustiani .; Lina Anatan . (Jurnal Manajemen Maranatha, 2010)
Corporate social responsibility (CSR) is a term describing a company's obligations to be accountable to all of its stakeholders in all its operations and activities. It is increasingly recognised as a source of competitive advantage, and thus a significant corporate resource, as well as an important part of how competitive relationships operate. Corporate has to give serious consideration to the society as non-commercial responsibilities. It implies that besides owners, investors and any shareholders, the concepts of business ethics and the importance of stakeholders should be considered by management. This approach is inextricably linked to the Triple Bottom Line through which the standard line of prosperity (or profit) should now be considered along with the bottom lines of planet (or environment) and people (or society).Keywords: corporate social responsibility, triple bottom line, competitive advantage.